ANALISIS PENGARUH TINGKAT PENDAPATAN PERKAPITA DAN PEMBENTUKAN MODAL TERHADAP PEREKONOMIAN DI PROVINSI JAMBI TAHUN 2016-2020 - Masrida Zasriati (Institut Agama Islam Negeri Kerinci, 2022)
This study aims to determine whether there is an effect of the level of income per capita and the level of capital formation on the economy in Jambi Province during the period 2011-2020. The research method used is a descriptive quantitative approach, the type of data used in this study is secondary data obtained from related agencies which are then processed using SPSS.25 software through tests related to research needs. The results of the study indicate that there is a positive and significant effect between per capita income and formation on ADHK GRDP in Jambi Province during 2011-2020 either partially or simultaneously. The magnitude of the influence given by Per capita Income and Capital Formation on GRDP ADHK is 68.7%.